The Influence of Green Marketing and Price Perception on Brand Image and Its Impact on Purchase Intention - Andreas P. Muljono; Metta Padmalia; Agoes Tinus Lis Indrianto (Journal Research of Social Science, Economics, and Management, 2025)
The increase in public awareness of environmental issues in recent years has prompted many companies to implement green marketing as part of their marketing strategy. Jago Coffee, as one of the pioneers in  the café-on-wheels concept  in Indonesia, uses an eco-friendly marketing strategy through collaboration with the environmental organization Bumiterra for forest reforestation in Borneo. The increasingly fierce competition in the coffee industry makes this research necessary to find out how Attitude to Green marketing and price perception affect  Jago Coffee's Brand Image, as well as its impact on  consumer Purchase Intention. The underlying theory of this research is the Theory of Planned Behavior (TPB). This study uses a quantitative method with survey techniques and involves 170 respondents who were selected through purposive sampling techniques. Data analysis was carried out using Structural Equation Modeling (SEM) to test the relationships between variables. Validity and reliability tests using Cronbach's Alpha and Composite Reliability are used to ensure that the instruments used are valid and reliable. The results of the study show that both Attitude to Green Marketing and Price Perception have a significant effect on Brand Image, and Brand Image has the strongest influence on Purchase Intention. Although these two variables also have a direct effect on Purchase Intention, they become stronger when mediated by Brand Image. Interestingly, Price Perception shows a weaker direct influence on Purchase Intention, indicating that cheap prices alone are not enough to drive purchases in the absence of a strong brand image.